ANALISIS REGRESI LINIER BERGANDA: KETEPATAN PENGIRIMAN DAN KEAMANAN BARANG SEBAGAI PREDIKTOR KEPUASAN PELANGGAN PADA KONSUMEN J&T KABUPATEN JEPARA - prasetyo, Iwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to analyze the extent to which the variables of delivery accuracy (X1) and product security (X2) influence customer satisfaction (Y) at J&T Express in Jepara. A quantitative method was applied with multiple regression analysis on 100 samples randomly selected through a questionnaire. Data processing using SPSS version 26 software revealed that delivery accuracy (X₁) had a positive and significant effect on customer satisfaction (β=0.968; p=0.000), while product security (X₂) was insignificant (β=-0.047; p=0.603). The Adjusted R² value of 0.796 indicates that 79.6% of the variation in customer satisfaction (Y) can be explained by these two variables: delivery accuracy (X1) and product security (X2). This study concludes the importance of optimizing delivery accuracy as a top priority without neglecting product security as a customer need. Keywords: customer satisfaction, delivery accuracy, product security